Modelling habitat suitability of the Himalayan monal (Lophophorus impejanus) and its connectivity in the Himalayas - Baral, Suraj (Nepalese Journal of Zoology, 2022)
The Himalayan monal Lophophorus impejanus is a montane bird exhibiting a seasonal migration to avoid harsh winter. However, the knowledge of the suitable habitat and level of connectivity across the range for the species is not available. To close this knowledge gap relevant for the species' conservation, species distribution modelling with presence-only data and relevant environmental variables was used to determine the range-wide distribution of the species. The distribution of the species is mainly constrained by habitat and climatic variables. The connectivity of the species was modeled using the distribution model output. The study presented a currently contiguous area of suitable habitat available for the species that are well connected with evidence of metapopulation in the range edges. The study also found that the current network of protected areas is not sufficient to ensure the connectivity of the species. Conservation of the currently suitable habitat is necessary to ensure the species is conserved.